WHAT IS KNOWN ABOUT TAX AMNESTY? A SCOPING REVIEW - Nina Sabnita (Politeknik Keuangan Negara STAN, 2019)
Scoping review is increasingly common approach for reviewing research evidence to address broader topic. This scoping study aims to review the literatures on tax amnesty program and describe the factors related to tax amnesty, such as implementations, costs and benefits, participation, and the effects of the program, and lesson learned from countries around the world. This review also provides some policy recommendations for policy makers to make it useful in reaching the objectives of the amnesty